1994
DOI: 10.1128/mcb.14.7.4947
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor GATA-4 regulates cardiac muscle-specific expression of the alpha-myosin heavy-chain gene.

Abstract: The alpha-myosin heavy-chain (alpha-MHC) gene is the major structural protein in the adult rodent myocardium. Its expression is restricted to the heart by a complex interplay of trans-acting factors and their cis-acting sites. However, to date, the factors that have been shown to regulate expression of this gene have also been found in skeletal muscle cells. Recently, transcription factor GATA-4, which has a tissue distribution limited to the heart and endodermally derived tissues, was identified. We recently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
196
0
5

Year Published

1997
1997
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 289 publications
(215 citation statements)
references
References 54 publications
14
196
0
5
Order By: Relevance
“…This site was selected for study because it has been shown to be important for the cardiac muscle-specific expression of the ␣-MHC, troponin C slow/cardiac , brain natriuretic peptide (BNP), and atrial natriuretic factor (ANF) genes (9,10,29,30). The latter is expressed in adult ventricular cardiac myocytes only in response to hypertrophic stimuli (22).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This site was selected for study because it has been shown to be important for the cardiac muscle-specific expression of the ␣-MHC, troponin C slow/cardiac , brain natriuretic peptide (BNP), and atrial natriuretic factor (ANF) genes (9,10,29,30). The latter is expressed in adult ventricular cardiac myocytes only in response to hypertrophic stimuli (22).…”
Section: Resultsmentioning
confidence: 99%
“…Site-specific mutations were introduced into the AT 1a R promoter cloned into pBluescript SK(Ϫ) by rolling circle PCR as previously described (10,16). Mutations in the AP-1 site were introduced using AT1R-APmut and AT-AP-PCR as primers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…GATA4 is a transcription factor that is found specifically in cardiac cell nuclei. Comparisons of the amounts of GATA4 (cardiac cell marker) to GATA2 (non-cardiac cell marker) can be used to show the relative enrichment of cardiac and non-cardiac cell nuclei (8,17,18).…”
Section: Selective Isolation Of Cardiac Cell Nuclei From Whole Heart mentioning
confidence: 99%
“…GATA4 is a transcription factor that is found specifically in cardiac cell nuclei. Comparisons of the amounts of GATA4 (cardiac cell marker) to GATA2 (non-cardiac cell marker) can be used to show the relative enrichment of cardiac and non-cardiac cell nuclei (8,17,18).The use of marker enzyme analyses for the purity of the nuclear preparations is particularly important in comparisons of nuclear phospholipids in hearts subjected to intense stress such as ischemia, ischemia/reperfusion and infarction. Under these conditions, the subcellular integrity could vary considerably, resulting in disparate isolation and purity of subcellular fractions.…”
mentioning
confidence: 99%